Supercritical Fluid Geochemistry in Geothermal Systems. (5th August 2019) - Heřmanská, Matylda; Kleine, Barbara I.; Stefánsson, Andri
Abstract : Supercritical fluids exist in the roots of many active high-temperature geothermal systems. Utilization of such supercritical resources may multiply energy production from geothermal systems; yet, their occurrence, formation mechanism, and chemical properties are poorly constrained. Flow-through experiments at 260°C and 400-420°C were performed to study the chemical and mineralogical changes associated with supercritical fluid formation near shallow magmatic intrusions by conductive heating and boiling of conventional subcritical geothermal fluids. Supercritical fluids formed by isobaric heating of liquid geothermal water had similar volatile element concentrations (B, C, and S) as the subcritical water. In contrast, mineral-forming element concentrations (Si, Na, K, Ca, Mg, and Cl) in the supercritical fluid were much lower. The results are consistent with the observed mineral deposition of quartz, aluminum silicates, and minor amount of salts during boiling. Similar concentration patterns have been predicted from geochemical modeling and were observed at Krafla, Iceland, for the IDDP-1 supercritical fluid discharge. The experimental results confirm previous findings that supercritical fluids may originate from conductive heating of subcritical geothermal reservoir fluids characterized by similar or lower elemental concentrations with minor input of volcanic gas.